Differential survival and reproduction in colour forms of Philaenus spumarius give new insights to the study of its balanced polymorphism - Silva, Sara E. (2017)
1. Colour polymorphisms are common across animals and are often the result of complex selection regimes. Philaenus spumarius (Linnaeus) (Hemiptera, Aphrophoridae) shows a widely studied dorsal colour polymorphism with several described phenotypes whose variation in their occurrence and frequency, as well as their maintenance across time, have been reported. Several selective influences have been suggested to play a role, but the mechanisms underlying the maintenance of this polymorphism are still poorly understood. 2. To explore the adaptive significance of the colour polymorphism of P. spumarius, an experiment was conducted in captivity under semi-natural conditions to measure survival, reproductive success, and duration of egg maturation. 3. It was found that there was higher longevity, a higher number of oviposition events, and a higher number of eggs laid by trilineatus phenotype females than by typicus and marginellus, supporting previous reports of an increase in trilineatus frequency during the season. The duration of egg maturation did not differ among phenotypes. 4. The higher longevity and fertility of the trilineatus phenotype may compensate, for example, the higher rate of attack by parasitoids and/or higher solar radiation reflectance in this phenotype, which have already been reported in previous studies, constituting a possible mechanism for the maintenance of this polymorphism.